The origin and activity of Yelets autocephaly in Orel diocese in the early 1920s: a history of resistance to the Renovationist Schism in the Russian Orthodox Church - Timofey Balyko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article discusses the process of creation in 1922-1923. Yelets autocephaly, whose leaders - as well as the leaders of the Petrograd, Ufa, Belev and Nizhny Tagil autocephalies - refused to recognize the authority of the renovationist "Supreme Church Administration" and continued to remain faithful to Patriarch Tikhon. The author of the study not only restores the history of the emergence and activity of the autocephalous Yelets diocesan administration in the Orel diocese that joined the Renovationists, but also reveals the features of the creation of the Yelets autocephaly in comparison with similar processes in other regions listed above. One of these features can be called the fact that in Yelets the creation of autocephaly, which began two weeks after the Renovationist coup in Moscow - at the end of May 1922, was already carried out by mid-September, and without the direct participation of the bishops who were imprisoned - by forces active parish clergy, who transferred the administration of autocephaly to Bishop Nikolai (Nikolsky) of Yelets, who was released in October 1922. The history of the Yelets diocesan administration went beyond the Oryol diocese and by 1923 reached the level of the highest executive authorities of the Soviet state. Yelets autocephaly was the only autocephaly considered in the article, created without the participation of bishops, by the forces of the clergy and laity - already in September 1922. The study of the example of self-organization of a part of the church people in Yelets during the schism of the 1920s, the study of the significance of church documents of 1917-1922 supporting the self-government of parishes and dioceses, acquires additional relevance for developing a strategy to minimize the spread of regional church-political unrest.